Penerapan Model Pembelajaran Cooperative Learning Tipe STAD (Student Team Achievement Division) untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Peserta Didik Kelas X-7 di SMA Negeri 2 Rantau Utara - Simalango, Ayu Yusnida (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the learning outcomes of students in the subject of Pancasila Education through the implementation of the STAD (Student Team Achievement Division) cooperative learning model. To achieve this goal, the research uses a classroom action research approach conducted in two cycles. The subjects of the research are students of class X-7 at SMA Negeri 2 Rantau Utara, totaling 36 people. The data collection techniques used include learning outcome tests, observation of learning activities, and documentation. The obtained data were analyzed quantitatively to see improvements in learning completeness, as well as qualitatively to evaluate the learning process. The results in the pre-cycle stage showed that the students' learning completeness only reached 13.8% with an average score of 54.8. After implementing the STAD learning model in cycle I, the completeness increased to 38.8% with an average score of 67.2, but it still had not reached the success indicator of ≥75% of students obtaining a score of ≥80. In cycle II, the learning outcomes significantly improved with an average score of 85.8 and a learning completeness of 88.8% or 32 students passing. Therefore, it can be concluded that the Cooperative Learning model type STAD is effective in improving the learning outcomes of Pancasila Education in 10th-grade students of SMA Negeri 2 Rantau Utara.